The Impact of Tobacco‐Free School Policies on Youth Smoking Rates in Florida Public School Districts. (February 2016) - Terry, Amanda; Zhang, Ning Jackie
ABSTRACT: BACKGROUND: Developing and implementing policies to curb and prevent youth tobacco use is of the utmost importance. In Florida, public school districts were authorized to develop tobacco‐free school policies through an amendment to the Florida Clean Indoor Air Act in 2011. The purpose of this study is to determine the impact of tobacco‐free school policies on smoking rates among youth in Florida. METHODS: Analysis of covariance (ANCOVA) and a multiple regression analysis were used to determine whether the comprehensiveness and enforcement of tobacco‐free school policies affect the youth smoking rates within Florida public school districts. The 2010 and 2014 youth smoking rates were calculated based on the Florida Youth Tobacco Survey results. RESULTS: The 2010 youth smoking rate and the inclusion of the enforcement component with provision of cessation resources were statistically significant predictors of the 2014 youth smoking rate. However, the comprehensiveness level of a policy and the inclusion of an enforcement component were not statistically significant predictors. CONCLUSIONS: The inclusion of an enforcement component with provision of cessation resources is important in efforts to reduce youth smoking rates. The content of the tobacco‐free school policies seems to be less relevant to their effectiveness than the enforcement of the policies.